2018
DOI: 10.1111/cei.13149
|View full text |Cite
|
Sign up to set email alerts
|

Stroma: the forgotten cells of innate immune memory

Abstract: SummaryAll organisms are exposed constantly to a variety of infectious and injurious stimuli. These induce inflammatory responses tailored to the threat posed. While the innate immune system is the front line of response to each stimulant, it has been considered traditionally to lack memory, acting in a generic fashion until the adaptive immune arm can take over. This outmoded simplification of the roles of innate and acquired arms of the immune system has been challenged by evidence of myeloid cells altering … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 87 publications
1
27
0
Order By: Relevance
“…It remains to be seen whether epithelial stem cells at other barrier sites, such as the intestine, can also be induced to retain memory through modifications of the epigenetic landscape. Finally, stromal cells, which include fibroblasts and endothelial cells, also show memory to previous stimuli (reviewed in Reference ). Coculture of macrophages with LPS‐trained bone marrow‐derived mesenchymal stem cells in vitro led to reduced proinflammatory and enhanced anti‐inflammatory responses in the macrophages, which was associated with epigenetic alterations in the mesenchymal stem cells mesenchymal stem cells .…”
Section: Microbiome and Innate Memorymentioning
confidence: 99%
“…It remains to be seen whether epithelial stem cells at other barrier sites, such as the intestine, can also be induced to retain memory through modifications of the epigenetic landscape. Finally, stromal cells, which include fibroblasts and endothelial cells, also show memory to previous stimuli (reviewed in Reference ). Coculture of macrophages with LPS‐trained bone marrow‐derived mesenchymal stem cells in vitro led to reduced proinflammatory and enhanced anti‐inflammatory responses in the macrophages, which was associated with epigenetic alterations in the mesenchymal stem cells mesenchymal stem cells .…”
Section: Microbiome and Innate Memorymentioning
confidence: 99%
“…Previous studies suggested that synovial fibroblasts function as sentinel cells that can sense tissue damage in the joint [25]. The process of tissue damage recognition by synovial fibroblasts is considered to occur through binding of DAMPs (damage-associated molecular patterns) to their receptors, such as TLR4 (Toll-like receptor 4) [25, 26]. Engagement of TLR4 activates MyD88 (myeloid differentiation primary response protein 88) signaling pathways within synovial fibroblasts which induce the release of various pro-inflammatory cytokines and chemokines [25, 27].…”
Section: Discussionmentioning
confidence: 99%
“…In their review, Crowley et al . present compelling evidence for the existence of innate immune memory in stromal cells. The authors discuss how stromal memory may exacerbate or restrain inflammatory disease.…”
mentioning
confidence: 80%
“…In recent years, the concept of innate immune memory, particularly in myeloid cells, has been catapulted into the limelight by the elegant work of Mihai Netea and coworkers. In their review, Crowley et al [3] present compelling evidence for the existence of innate immune memory in stromal cells. The authors discuss how stromal memory may exacerbate or restrain inflammatory disease.…”
mentioning
confidence: 99%